Perkembangan Historis Ilmu Shorof : Analisis Kontribusi Ulama Klasik Terhadap Sistematika Morfologi Bahasa Arab - Neng Suryanti (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
This study aims to examine the historical development of the science of shorof with a focus on the contribution of classical scholars to the systematics of Arabic morphology, especially in the infaʽala verb pattern. Using a qualitative approach and literature study methods, this study traces the linguistic thoughts of figures such as Sībawayh, al-Mubarrid, Ibn Jinnī, to al-Raḍī. The results of the study show that the majority of classical scholars determine the infaʽala pattern as a non-transitive verb (lāzim) that contains the meaning of muṭāwaʽah, and is closely related to the basic pattern of faʽala. In addition, there were restrictions on certain letters as basic letters in this pattern to avoid sound assimilation (idghām). This study confirms that the Arabic morphological system is built on regular and logical rules, and the contribution of classical scholars is very significant in laying the scientific foundations of the science of shorof which are still relevant today